Design estratégico e afrofuturismo na busca por uma moda decolonial sustentável - Anchieta, Carolina (Universidade do Vale do Rio dos Sinos, 2021)
An innovative future in the context of sustainable fashion corresponds to the comprehension that sustainability also permeates the transformation of unequal realities and the strengthening of all the agents involved in this system. In Brazil, where over half of the population is black, sustainability needs to consider the specificities related to race and all the social consequences inherited from slavery and, thus, contribute to the systemic discontinuity in structural racism. Social innovation, in the study of design, is perceived mainly from the involved agents and their social demands. But how is it possible to innovate when the field of design does not comprehend its social role in a mostly black country, nor does it recognize the importance of black presence in protagonist roles in innovation? We recognize in Afrofuturism – a multicultural movement that proposes a return to the past as a form of reinventing history and retelling it through a decolonial lens – a potential for projects which can, oriented by design, promote social innovation, though the projection of future scenarios, and the uplifting of black people through fashion. Thus, the general objective of this research is to explore the potentialities of Afrofuturism, as a space to project potent black futures, allied to the principles of strategic design, to give new meaning to sustainable fashion. The methodology is a case study on the brand LAB, created by the rapper Emicida and his brother, fellow musician Evandro Fióti. We analyzed how LAB promotes systemic discontinuities in structural racism, inspired by ancestries, aquilombamento, and Afrofuturism. Through this analysis, we created a workshop for black people, divided into an asynchronous stage, which included the development of an Afrofuturistic Immersion Platform, and a synchronous stage, with the of imagining of settings through Afrofuturism. We believe that decolonial and sustainable fashion is achievable, through the strengthening of elements of identity, with the reconnection to ancestry promoted by Afrofuturism and, thus, the designing of innovative black futures.
Keywords: Design estratégico; Afrofuturismo; Moda decolonial sustentável; Strategic design; Afrofuturism; Decolonial sustainable fashion; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial